Keberkesanan dasar kadar pertukaran tetap dalam mengkesampingkan faktor luar di BSKL - Tamat Sarmidi; Abu Hassan Shaari Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2001)
The main purpose of this paper is to analyze the impact of Malaysian selective capital control policy on the international transmission of stock price movement and international market integration. Empirical study was done on two different time regimes, i.e. before capital control (January 1995 until May 1997) and after capital control (September 1998 until December 1999). Vector Autoregressive (VAR) model including Johansen-Juselius multivariate cointegration test, vector error-correction model (VECM), and impulse response functions (IRFs) were utilised. The above econometric methods together with ECTs are capable of detecting the impact of external forces on domestic stock markets. The results showed that after the capital control policy was imposed, the integration between equity markets is still maintained with a greater and wilder responses